The Plasmonic Resonances of a Bowtie Antenna (Analysis in Theory and Applications, 2022)
Metallic bowtie-shaped nanostructures are very interesting objects in optics, due to their capability of localizing and enhancing electromagnetic fields in the vicinity of their central neck. In this article, we investigate the electrostatic plasmonic resonances of two-dimensional bowtie-shaped domains by looking at the spectrum of their Poincaré variational operator. In particular, we show that the latter only consists of essential spectrum and fills the whole interval $[0,1]$. This behavior is very different from what occurs in the counterpart situation of a bowtie domain with only close-to-touching wings, a case where the essential spectrum of the Poincaré variational operator is reduced to an interval $σ_{ess}$ strictly containing in $[0,1]$. We provide an explanation for this difference by showing that the spectrum of the Poincaré variational operator of bowtie-shaped domains with close-to-touching wings has eigenvalues which densify and eventually fill the remaining parts of $[0,1] \setminus σ_{ess} $ as the distance between the two wings tends to zero.
Keywords: Neumann-Poincaré operator; corner singularity; spectrum; resonance.